1987
DOI: 10.1093/sleep/10.suppl_1.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flurazepam and Zopiclone on the Performance of Chronic Insomniac Patients: A Study of Ethanol-Drug Interaction

Abstract: Three groups of ten middle-aged insomniac patients were treated with placebo, flurazepam, or zopiclone for 12 consecutive days in a study designed to compare the residual daytime effects of long-acting flurazepam and short-acting zopiclone on a variety of cognitive and motor tasks. These effects were examined independently and in combination with ethanol effects. The effects of the drugs on sleep parameters were also subjectively assessed by means of questionnaires during treatment and withdrawal. The study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Morning impairment of psychomotor performance after night-time zopiclone 7.5mg administration is similar to that observed after administration of nitrazepam 5 to 10mg (Goa & Heel 1986), but less than that occurring after flurazepam 15 to 30mg (Goa-& Heel 1986;Mamelak et al 1987;Singh & Bourgouin 1990).…”
Section: Effects On Psychomotor Function and Memorysupporting
confidence: 60%
See 1 more Smart Citation
“…Morning impairment of psychomotor performance after night-time zopiclone 7.5mg administration is similar to that observed after administration of nitrazepam 5 to 10mg (Goa & Heel 1986), but less than that occurring after flurazepam 15 to 30mg (Goa-& Heel 1986;Mamelak et al 1987;Singh & Bourgouin 1990).…”
Section: Effects On Psychomotor Function and Memorysupporting
confidence: 60%
“…Psychomotor function was not impaired the morning after night-time administration of zopiclone 7.5mg in middle-aged patients (mean age 50 years) with insomnia (Mamelak et al 1987) or in elderly patients (aged 68 to 94 years) with insomnia given up to 10mg on retiring (Dehlin et al 1983). Psychomotor function was not impaired the morning after night-time administration of zopiclone 7.5mg in middle-aged patients (mean age 50 years) with insomnia (Mamelak et al 1987) or in elderly patients (aged 68 to 94 years) with insomnia given up to 10mg on retiring (Dehlin et al 1983).…”
Section: Effects On Psychomotor Function and Memorymentioning
confidence: 99%
“…In 4 out of the 44 experimental studies, ethanol was used as a comparator drug for zopiclone impairment [23,71,77,78,84,85]. (The 4 studies were reported in 6 manuscripts.)…”
Section: Current Knowledge On Zopiclone and Traffic Accident Riskmentioning
confidence: 99%
“…98,100,101,105,109,149,[152][153][154][161][162][163][164][165][166][167] No studies contained data adequate for meta-analysis. No meta-analysis of harms was possible.…”
Section: Discussionmentioning
confidence: 99%